MRI and Infantile-Onset Leukoencephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at VU University Medical Center, Amsterdam and other international centers reviewed the MRIs of >3000 patients with an unclassified leukoencephalopathy, and 7 patients (3 male) shared similar MRI abnormalities and clinical and laboratory finding